SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN GURU TERBAIK MENGGUNAKAN METODE MAUT DENGAN PEMBOBOTAN ROC (STUDI KASUS: SDN 101883 PASAR XIII) - Nst, Rizky Perdana; Sembiring, Abdul Sani; Ningsih, Trans (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Selecting the best teacher is crucial in the field of education as it motivates educators who have taught students and allows for recognition of their efforts. However, currently, the data collection process is poorly organized, leading to suboptimal outcomes in identifying the best teachers. Therefore, this study uses a decision support system applying the Multi-Attribute Utility Theory (MAUT) to calculate the competency scores for each teacher and rank them accordingly. MAUT, which stands for Multi-Attribute Utility Theory, is used for decision-making by identifying relevant attributes and assigning weights to each attribute based on its importance. The implementation of a decision support system using MAUT is expected to assist in accurately and effectively determining the best teacher at SDN 101883 Pasar XIII. This research aids SDN 101883 Pasar XIII in making structured, accurate decisions regarding the selection of the best teacher. The study results indicate that Salome Pandiangan, S.Pd, with a score of 0.818975, is identified as the best teacher at SDN 101883 Pasar XIII.